Manufacturing process and etching solution of AG glass display panel with skin feeling effect
Through chemical acid etching technology, a micron-level bee-eye-like microcrystalline particle layer is generated on the glass surface, which solves the problem that existing skin-feeling films or paints are not resistant to scratches, and achieves a silky and soft skin-feeling effect on the glass surface, and has multiple skin-feeling effects. Excellent performance.
Patent Information
- Application Number
- CN202411443803.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
AI Technical Summary
When obtaining skin-sensing effects, the existing smart control panel and smart product shell are not resistant to scratches when using skin-sensing masks or skin-sensing paints, and are low in firmness. They are prone to scratches after long-term use, resulting in visual discomfort.
Using chemical acid etching technology, an etching solution containing ammonium fluoride, aluminum fluoride, phosphoric acid and other components is used to form a micron-scale bee-eye-like microcrystalline particle adhesion layer on the glass surface. Through stirring and maturation, combined with polishing steps, a silky smoothness is formed. Soft skin feeling effect.
It realizes a smooth, delicate, soft and full tactile feeling on the glass surface, and also has excellent properties such as anti-reflective light, scratch resistance, high wear resistance, dust resistance, and fingerprint resistance.
Smart Images

Figure CN119320240A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of glass panel manufacturing, and specifically relates to a manufacturing process and etching solution for a skin-feel effect AG glass display panel. Background Art
[0002] With the continuous advancement of science and technology and the continuous improvement of people's living standards, people have higher and higher requirements for comfort when they have close contact with smart digital products. This requires that the surfaces of various smart products that come into contact with the skin have a skin-like tactile feeling to satisfy people's pleasant and comfortable feeling when interacting with smart digital products.
[0003] However, currently, in order to obtain the skin-feel effect, the surface of the smart control panel and the shell of the smart product are treated with skin-feel film or skin-feel paint. Such products are not scratch-resistant and have low firmness. After long-term use, the surface is easily scratched, which brings visual discomfort to the user. The present invention adopts chemical acid etching technology to generate an etching layer with a skin-feel surface effect on the glass surface. When the product surface interacts with the human body, it produces a smooth, delicate, soft and plump velvety feeling and a warm tactile feeling like skin. At the same time, it has various excellent properties such as anti-reflective light, anti-scratch, high wear resistance, anti-dust, and anti-fingerprint. Summary of the invention
[0004] The purpose of the present invention is to provide a manufacturing process and etching solution for a skin-feel effect AG glass display panel in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: an etching solution for an AG glass display panel with a skin-feel effect, comprising 15%-25% ammonium fluoride, 3%-10% aluminum fluoride, 15%-25% phosphoric acid, 2%-8% trifluoroacetic acid, 2%-8% ammonium fluorosilicate, 2%-5% sodium acetate, 2%-5% cupric chloride, 0.5%-1.5% ferric nitrate, 0.2%-0.5% sodium benzoate, 0.1%-0.5% p-aminobenzenesulfonic acid, 3%-5% polyethylene glycol, 0.5%-1.5% sodium carboxymethyl cellulose, and 25%-40% water.
[0006] In a preferred embodiment, a manufacturing process of a skin-feel effect AG glass display panel comprises the following steps:
[0007] S1: accurately weighing various raw materials for preparing the etching solution as claimed in claim 1 in a set order;
[0008] S2: Turn on the mixer to stir, the stirring speed is 100-200 rpm, the stirring temperature is 15-20° C., and the stirring time is 3-5 hours;
[0009] S3: After the stirring is completed, the glass etching solution with skin-feel effect is prepared by standing and ripening for 72 hours at a constant temperature of 20°C;
[0010] S4: The glass surface that does not need to be etched is protected by a coating, the glass surface that needs to be etched is cleaned, and then the glass is vertically placed in the well-stirred etching solution;
[0011] S5: The etching time is 3 to 5 minutes. After the etching is completed, the glass is taken out from the etching solution, and then the residual solution on the surface of the glass is cleaned with pure water;
[0012] S6: Put the cleaned etched glass into a polishing pool for polishing for 10-15 minutes;
[0013] S7: Take out the polished glass and clean it with pure water. After air drying, the skin-feel effect glass is obtained.
[0014] In a preferred embodiment, in step S1, the weighing and adding order is: water → phosphoric acid → trifluoroacetic acid → ammonium fluoride → aluminum fluoride → ammonium fluorosilicate → sodium acetate → cupric chloride → ferric nitrate → sodium benzoate → p-aminobenzenesulfonic acid → polyethylene glycol → sodium carboxymethyl cellulose, and placed in a PVC container.
[0015] In a preferred embodiment, in step S1, an analytical balance with an accuracy of ±0.01 g is used for weighing. During the weighing process, the indoor temperature is controlled at 20±2°C and the relative humidity is controlled at 40%-60%. The raw materials should be stored in a dry and clean environment to avoid moisture absorption or contamination. After each raw material is weighed, it should be immediately sealed and stored to prevent changes in the properties of the raw material.
[0016] In a preferred embodiment, in step S2, the stirrer uses a double-shaft stirring paddle with a blade diameter of 200 mm and a stirring barrel capacity of not less than 100 L. The stirring speed is set to 150 rpm to ensure uniform mixing. During the stirring process, a constant temperature water bath is used to maintain the temperature in the stirring barrel at 18°C ± 2°C. The operating stability of the stirrer needs to be monitored by real-time monitoring equipment.
[0017] In a preferred embodiment, in step S3, the ambient temperature is controlled at 20°C ± 1°C by precision air conditioning, and the relative humidity is controlled at 50%-60%. The aging container is made of polypropylene that does not react with the etching solution, and the volume is not less than 200 L. During the aging period, the container needs to be sealed, and the ambient temperature and humidity are recorded regularly.
[0018] In a preferred embodiment, in step S4, the coating protection material uses a PET coating with a thickness of 50-100 μm. When cleaning the glass surface, use deionized water with a resistivity of not less than 1 MΩ·cm. After cleaning, there should be no water droplets on the glass surface and it should be blown dry with compressed air.
[0019] In a preferred embodiment, in step S5, the temperature of the etching solution should be controlled at 18°C ± 2°C. The speed of the glass moving up and down in the etching solution is 0.5-1 m / min to ensure uniform etching. After etching, the glass surface is rinsed with flowing pure water with a resistivity of ≥15MΩ·cm for no less than 2 minutes.
[0020] In a preferred embodiment, in step S6, the temperature of the polishing pool is controlled at 25°C ± 5°C, and the pH value of the polishing liquid is 8-10. The particle size of the abrasive is selected in the range of 1-3 μm, and the concentration of the polishing liquid is adjusted according to the abrasive particle size, generally 5%-10%. During the polishing process, the rotation speed of the glass is 30-50 rpm.
[0021] In a preferred embodiment, in step S7, when cleaning the polished glass, an ultrasonic cleaner is used, the water temperature is controlled at 40°C ± 5°C, and the ultrasonic frequency is 40kHz. The cleaning time is not less than 5 minutes to ensure that the polishing liquid and abrasive are completely removed. During the air drying process, the indoor temperature is controlled at 25°C ± 5°C, the relative humidity is controlled at 30%-50%, and the wind speed does not exceed 5m / s to prevent dust and fiber adhesion.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0023] In the present invention, the etching liquid reacts with the glass surface to generate a micron-sized bee-eye-shaped microcrystalline particle attachment layer on the glass surface. These microcrystalline particles are arranged in a concave-convex texture similar to the bee-eye structure. Since the upper surfaces of these micron-sized bee-eye-shaped microcrystalline particles are relatively full and round, the transition of the particle edges is natural and smooth, so that the frosted surface of the glass achieves a silky and smooth effect, and produces a subjective perception of smoothness, fineness, and warmth like skin when in contact with the human body, thereby achieving a skin-like skin-like effect on the glass surface. The chemical acid etching technology is used to generate an etching layer with a skin-like surface effect on the glass surface. When the product surface interacts with the human body, it produces a smooth, fine, soft and full velvety feeling and a warm tactile feeling like skin, and at the same time has various excellent properties such as anti-reflection light, anti-scratch, high wear resistance, anti-dust, and anti-fingerprint. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the process principle of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] Reference Figure 1 ,
[0027] The invention discloses an etching solution for an AG glass display panel with a skin-feeling effect, comprising 15%-25% of ammonium fluoride, 3%-10% of aluminum fluoride, 15%-25% of phosphoric acid, 2%-8% of trifluoroacetic acid, 2%-8% of ammonium fluorosilicate, 2%-5% of sodium acetate, 2%-5% of cupric chloride, 0.5%-1.5% of ferric nitrate, 0.2%-0.5% of sodium benzoate, 0.1%-0.5% of p-aminobenzenesulfonic acid, 3%-5% of polyethylene glycol, 0.5%-1.5% of sodium carboxymethyl cellulose and 25%-40% of water.
[0028] The production process includes the following steps:
[0029] S1: accurately weighing various raw materials for preparing the etching solution as claimed in claim 1 in a set order;
[0030] S2: Turn on the mixer to stir, the stirring speed is 100-200 rpm, the stirring temperature is 15-20° C., and the stirring time is 3-5 hours;
[0031] S3: After the stirring is completed, the glass etching solution with skin-feel effect is prepared by standing and ripening for 72 hours at a constant temperature of 20°C;
[0032] S4: The glass surface that does not need to be etched is protected by a coating, the glass surface that needs to be etched is cleaned, and then the glass is vertically placed in the well-stirred etching solution;
[0033] S5: The etching time is 3 to 5 minutes. After the etching is completed, the glass is taken out from the etching solution, and then the residual solution on the surface of the glass is cleaned with pure water;
[0034] S6: Put the cleaned etched glass into a polishing pool for polishing for 10-15 minutes;
[0035] S7: Take out the polished glass and clean it with pure water. After air drying, the skin-feel effect glass is obtained.
[0036] In step S1, the order of weighing and adding is: water → phosphoric acid → trifluoroacetic acid → ammonium fluoride → aluminum fluoride → ammonium fluorosilicate → sodium acetate → cupric chloride → ferric nitrate → sodium benzoate → p-aminobenzenesulfonic acid → polyethylene glycol → sodium carboxymethyl cellulose, and placed in a PVC container.
[0037] In step S1, an analytical balance with an accuracy of ±0.01g is used for weighing. During the weighing process, the indoor temperature is controlled at 20±2°C and the relative humidity is controlled at 40%-60%. The raw materials should be stored in a dry and clean environment to avoid moisture absorption or contamination. After each raw material is weighed, it must be sealed and stored immediately to prevent changes in the properties of the raw material.
[0038] In step S2, the mixer uses a double-shaft stirring paddle with a blade diameter of 200 mm and a stirring barrel capacity of not less than 100 L. The stirring speed is set to 150 rpm to ensure uniform mixing. During the stirring process, a constant temperature water bath is used to maintain the temperature in the stirring barrel at 18°C ± 2°C. The operating stability of the mixer needs to be monitored by real-time monitoring equipment.
[0039] In step S3, the ambient temperature is controlled at 20°C ± 1°C by precision air conditioning, and the relative humidity is controlled at 50%-60%. The aging container is made of polypropylene that does not react with the etching solution, and the volume is not less than 200L. During the aging period, the container needs to be sealed, and the ambient temperature and humidity are recorded regularly.
[0040] In step S4, the coating protection material uses a PET coating with a thickness of 50-100 μm. When cleaning the glass surface, use deionized water with a resistivity of not less than 1 MΩ·cm. After cleaning, there should be no water droplets on the glass surface and it should be blown dry with compressed air.
[0041] In step S5, the temperature of the etching solution should be controlled at 18°C ± 2°C. The glass moves up and down in the etching solution at a speed of 0.5-1m / min to ensure uniform etching. After etching, the glass surface is rinsed with flowing pure water with a resistivity of ≥15MΩ·cm for no less than 2 minutes.
[0042] In step S6, the temperature of the polishing pool is controlled at 25°C ± 5°C, and the pH value of the polishing liquid is 8-10. The particle size of the abrasive is selected in the range of 1-3 μm, and the concentration of the polishing liquid is adjusted according to the abrasive particle size, generally 5%-10%. During the polishing process, the rotation speed of the glass is 30-50 rpm.
[0043] In step S7, when cleaning the polished glass, use an ultrasonic cleaner with the water temperature controlled at 40°C ± 5°C and the ultrasonic frequency at 40kHz. The cleaning time is not less than 5 minutes to ensure that the polishing liquid and abrasive are completely removed. During the air drying process, the indoor temperature is controlled at 25°C ± 5°C, the relative humidity is controlled at 30%-50%, and the wind speed does not exceed 5m / s to prevent dust and fiber adhesion.
[0044] Embodiment 1:
[0045] 1. Prepare etching solution according to the raw material composition (wt%): 20% ammonium fluoride, 8% aluminum fluoride, 22% phosphoric acid, 3% trifluoroacetic acid, 5% ammonium fluorosilicate, 2% sodium acetate, 3% cupric chloride, 0.5% ferric nitrate, 0.3% sodium benzoate, 0.3% p-aminobenzenesulfonic acid, 5% polyethylene glycol, 0.5% sodium carboxymethyl cellulose, and 30.4% water; accurately weigh various raw materials in sequence according to the set order, and the weighing and adding order is: water → phosphoric acid → trifluoroacetic acid → ammonium fluoride → aluminum fluoride → ammonium fluorosilicate → sodium acetate → cupric chloride → ferric nitrate → sodium benzoate → p-aminobenzenesulfonic acid → polyethylene glycol → sodium carboxymethyl cellulose, and place them in a PVC container.
[0046] 2. Turn on the mixer and stir at a speed of 200 rpm, a temperature of 20°C, and a stirring time of 3 hours.
[0047] 3. After stirring, place the mixture in a constant temperature environment of 20°C for 72 hours to prepare the glass etching liquid with skin-feel effect.
[0048] 4. Protect the glass surface that does not need to be etched with a film, clean the glass surface that needs to be etched, and then place the glass vertically into the evenly stirred etching solution.
[0049] 5. The etching time is 5 minutes. After etching, take the glass out of the etching solution, and then clean the residual solution on the glass surface with pure water.
[0050] 6. Put the cleaned etched glass into the polishing pool for polishing for 10 minutes.
[0051] 7. Take out the polished glass and clean it with pure water. After air drying, the skin-feel glass will be obtained.
[0052] Example 2
[0053] 1. Prepare etching solution according to the raw material composition (wt%): 22% ammonium fluoride, 6% aluminum fluoride, 20% phosphoric acid, 4.5% trifluoroacetic acid, 4.5% ammonium fluorosilicate, 2.5% sodium acetate, 3.5% cupric chloride, 1.0% ferric nitrate, 0.3% sodium benzoate, 0.5% p-aminobenzenesulfonic acid, 4% polyethylene glycol, 1.0% sodium carboxymethyl cellulose, and 30.2% water; accurately weigh various raw materials in sequence according to the set order, and the weighing and adding order is: water → phosphoric acid → trifluoroacetic acid → ammonium fluoride → aluminum fluoride → ammonium fluorosilicate → sodium acetate → cupric chloride → ferric nitrate → sodium benzoate → p-aminobenzenesulfonic acid → polyethylene glycol → sodium carboxymethyl cellulose, and place them in a PVC container.
[0054] 2. Turn on the mixer and stir at a speed of 180 rpm, a temperature of 20°C, and a stirring time of 5 hours.
[0055] 3. After stirring, place the mixture in a constant temperature environment of 20°C for 72 hours to prepare the glass etching liquid with skin-feel effect.
[0056] 4. Protect the glass surface that does not need to be etched with a film, clean the glass surface that needs to be etched, and then place the glass vertically into the evenly stirred etching solution.
[0057] 5. The etching time is 4 minutes. After etching, take the glass out of the etching solution, and then clean the residual solution on the glass surface with pure water.
[0058] 6. Put the cleaned etched glass into the polishing pool for polishing for 15 minutes.
[0059] 7. Take out the polished glass and clean it with pure water. After air drying, the skin-feel glass will be obtained.
[0060] Example 3
[0061] 1. Prepare etching solution according to the raw material composition (wt%): 24% ammonium fluoride, 3% aluminum fluoride, 21.5% phosphoric acid, 2.5% trifluoroacetic acid, 6% ammonium fluorosilicate, 2.5% sodium acetate, 1.5% cupric chloride, 1.0% ferric nitrate, 0.5% sodium benzoate, 0.3% p-aminobenzenesulfonic acid, 6% polyethylene glycol, 0.6% sodium carboxymethyl cellulose, and 30.6% water; accurately weigh various raw materials in sequence according to the set order, and the weighing and adding order is: water → phosphoric acid → trifluoroacetic acid → ammonium fluoride → aluminum fluoride → ammonium fluorosilicate → sodium acetate → cupric chloride → ferric nitrate → sodium benzoate → p-aminobenzenesulfonic acid → polyethylene glycol → sodium carboxymethyl cellulose, and place them in a PVC container.
[0062] 2. Turn on the mixer and stir at a speed of 150 rpm, a temperature of 20°C, and a stirring time of 4 hours.
[0063] 3. After stirring, place the mixture in a constant temperature environment of 20°C for 72 hours to prepare the glass etching liquid with skin-feel effect.
[0064] 4. Protect the glass surface that does not need to be etched with a film, clean the glass surface that needs to be etched, and then place the glass vertically into the evenly stirred etching solution.
[0065] 5. The etching time is 3 minutes. After etching, take the glass out of the etching solution, and then clean the residual solution on the glass surface with pure water.
[0066] 6. Put the cleaned etched glass into the polishing pool for polishing for 12 minutes.
[0067] 7. Take out the polished glass and clean it with pure water. After air drying, the skin-feel glass will be obtained.
[0068] The comparison of the data before and after etching of the above embodiments 1 to 3 is shown in the following table:
[0069] performance Glass original Implementation 1 Implementation 2 Implementation 3 Roughness(μm) 0 0.35 0.30 0.38 Light transmittance (%) 98 78.6 79.3 78.2 Glossiness(%) 118 60.5 60.8 59.8 Haze(%) 0 30.8 30.2 31.3
[0070] From the above, it can be known that in the present invention, the etching liquid reacts with the glass surface to generate a micron-sized bee-eye-shaped microcrystalline particle attachment layer on the glass surface. These microcrystalline particles are arranged in a concave-convex texture similar to the bee-eye structure. Since the upper surfaces of these micron-sized bee-eye-shaped microcrystalline particles are relatively full and round, the transition of the particle edges is natural and smooth, so that the frosted surface of the glass achieves a silky and smooth effect, and produces a subjective perception of smoothness, fineness, and warmth like skin when in contact with the human body, thereby achieving a skin-like skin-like effect on the glass surface. The chemical acid etching technology is used to generate an etching layer with a skin-like surface effect on the glass surface. When the product surface interacts with the human body, it produces a smooth, fine, soft and full velvety feeling and a warm tactile feeling like skin, and at the same time has various excellent properties such as anti-reflection light, anti-scratch, high wear resistance, anti-dust, and anti-fingerprint.
[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0072] The above description enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An etching solution for a skin-feeling AG glass display panel, characterized in that: The invention comprises 15%-25% of ammonium fluoride, 3%-10% of aluminum fluoride, 15%-25% of phosphoric acid, 2%-8% of trifluoroacetic acid, 2%-8% of ammonium fluorosilicate, 2%-5% of sodium acetate, 2%-5% of cupric chloride, 0.5%-1.5% of ferric nitrate, 0.2%-0.5% of sodium benzoate, 0.1%-0.5% of p-aminobenzenesulfonic acid, 3%-5% of polyethylene glycol, 0.5%-1.5% of sodium carboxymethyl cellulose and 25%-40% of water.
2. A manufacturing process of a skin-feeling AG glass display panel, characterized in that: The manufacturing process comprises the following steps: S1: accurately weighing various raw materials for preparing the etching solution as claimed in claim 1 in a set order; S2: Turn on the mixer to stir, the stirring speed is 100-200 rpm, the stirring temperature is 15-20° C., and the stirring time is 3-5 hours; S3: After the stirring is completed, the glass etching solution with skin-feel effect is prepared by standing and ripening for 72 hours at a constant temperature of 20°C; S4: The glass surface that does not need to be etched is protected by a coating, the glass surface that needs to be etched is cleaned, and then the glass is vertically placed in the well-stirred etching solution; S5: The etching time is 3 to 5 minutes. After the etching is completed, the glass is taken out from the etching solution, and then the residual solution on the surface of the glass is cleaned with pure water; S6: Put the cleaned etched glass into a polishing pool for polishing for 10-15 minutes; S7: Take out the polished glass and clean it with pure water. After air drying, the skin-feel effect glass is obtained.
3. The manufacturing process of the skin-feeling AG glass display panel according to claim 2, characterized in that: In the step S1, the weighing and adding order is: water→phosphoric acid→trifluoroacetic acid→ammonium fluoride→aluminum fluoride→ammonium fluorosilicate→sodium acetate→copper chloride→ferric nitrate→sodium benzoate→para-aminobenzenesulfonic acid→polyethylene glycol→sodium carboxymethyl cellulose, and placed in a PVC container.
4. The manufacturing process of the skin-feeling effect AG glass display panel according to claim 2, characterized in that: In step S1, an analytical balance with an accuracy of ±0.01g is used for weighing; during the weighing process, the indoor temperature is controlled at 20±2°C and the relative humidity is controlled at 40%-60%; the raw materials should be stored in a dry and clean environment to avoid moisture absorption or contamination; after each raw material is weighed, it must be sealed and stored immediately.
5. The manufacturing process of the skin-feeling effect AG glass display panel according to claim 2, characterized in that: In step S2, the mixer uses a double-shaft stirring paddle with a blade diameter of 200 mm and a stirring barrel capacity of not less than 100 L; the stirring speed is set to 150 rpm to ensure uniform mixing; during the stirring process, a constant temperature water bath is used to maintain the temperature in the stirring barrel at 18°C ± 2°C; the operating stability of the mixer needs to be monitored by real-time monitoring equipment.
6. The manufacturing process of the skin-feeling AG glass display panel according to claim 2, characterized in that: In step S3, the ambient temperature is controlled at 20°C ± 1°C by precision air conditioning, and the relative humidity is controlled at 50%-60%; the aging container is made of polypropylene material that does not react with the etching solution, and the volume is not less than 200L; during the aging period, the container needs to be sealed, and the ambient temperature and humidity are recorded regularly.
7. The manufacturing process of the skin-feeling effect AG glass display panel according to claim 2, characterized in that: In step S4, the coating protection material uses a PET coating with a thickness of 50-100 μm; when cleaning the glass surface, deionized water is used, and the resistivity is not less than 1 MΩ·cm; after cleaning, there should be no water droplets on the glass surface, and it is blown dry with compressed air.
8. The manufacturing process of the skin-feel effect AG glass display panel according to claim 2, characterized in that: In step S5, the temperature of the etching solution should be controlled at 18°C ± 2°C; the speed of the glass moving up and down in the etching solution is 0.5-1m / min to ensure uniform etching; after etching, the glass surface is rinsed with flowing pure water with a resistivity of ≥15MΩ·cm, and the rinsing time is not less than 2 minutes.
9. The manufacturing process of the skin-feeling AG glass display panel according to claim 2, characterized in that: In step S6, the temperature of the polishing pool is controlled at 25°C ± 5°C, and the pH value of the polishing liquid is 8-10; the particle size of the abrasive is selected within the range of 1-3 μm, and the concentration of the polishing liquid is adjusted according to the abrasive particle size, generally 5%-10%; during the polishing process, the rotation speed of the glass is 30-50 rpm.
10. The manufacturing process of the skin-feel effect AG glass display panel according to claim 2, characterized in that: In step S7, when cleaning the polished glass, an ultrasonic cleaner is used, the water temperature is controlled at 40°C ± 5°C, and the ultrasonic frequency is 40kHz; the cleaning time is not less than 5 minutes to ensure that the polishing liquid and abrasive are completely removed; during the air-drying process, the indoor temperature is controlled at 25°C ± 5°C, the relative humidity is controlled at 30%-50%, and the wind speed does not exceed 5m / s to prevent dust and fiber adhesion.
Citation Information
Cited By
Preparation method of quantum dot skin-feeling glass decoration panel
CN120664787A